The effect of Tea Misletoe (Scurrula oortiana) Stem Extract as Immuno-Modulator on Oncogenic Marekâs Disease Virus Infection - Samsi, Mulyoto; Malole, MBM; Manalu, W; Handharjani, E (ANIMAL PRODUCTION, 2007)
Marekâs disease virus (MDV) is one of oncogenic herpesvirus. It causes immunosupresion and cancer in chicken. Several plants produce bioactive compounds which are very useful for treatment of many disease, especially hiperproliveration and virus infection. This study was aimed to find out mechanism of immuno-modulatory capacity in layer commercial chicken administered orally with extract of tea parasite (Scurrula oortiana) in dose of 10 mg/kg BW through drinking water, then the chicken were infected by intraperitoneal oncogenic MDV in dose of 1,0 x103 TCID50. The study used 60 layer commercial day old chicks (DOC) divided into four group treatments. The treatments were group A (administered S. oortiana extract and without MDV infection), B (neither S. oortiana nor MDV infection), C (administered S. oortiana extract and with MDV infection), and D (without administered S. oortiana extract, but with MDV infection). Results showed that MDV oncogenic caused immunosupresion at a day post infection (p.i) and recovery to be normal based on relative weight of bursa Fabricius and thymus at 40 days p.i. The extract of S. oortiana had a capability as an immunomodulator indicated by the increase of relative weight of bursa Fabricius and thymus at day 20 days p.i. (Animal Production 9(2): 172-177 (2007)Â Key Words: Marekâs disease virus (MDV), Scurrula oortiana, immuno-modulator